Multi-UAV Cooperative Suspension Control Strategy Considering Variable Rope Length and Load Posture Coupling Effect - Yi Wang; Kang Li; Xuefu Li; Jingyu Wang; Pengbo Yu (IEEE Access)
This paper addresses the issues of insufficient model accuracy and poor control performance in traditional unmanned aerial vehicle (UAV) lifting operations by proposing an improved control strategy for multi-UAV cooperative lifting operations and optimizing the dynamic model. Firstly, the efficiency of the operation is enhanced, by introducing multi-UAV cooperative lifting control. On this basis, the traditional dynamic model is improved, with a focus on the impact of variable rope length, analyzing the dynamic coupling relationship between rope length and swing angle, and constructing related coupling error functions to improve the stability and control accuracy of the system. At the same time, the interaction between the load and the swing is studied, considering the velocity relationship between the suspension point and the load, and taking into account the coupled effect of the load attitude. Finally, a Lagrangian dynamic model that includes multiple-UAV, variable rope length, and load-coupled effects is established. Based on the improved model, this paper proposes a coupled error function, designs a nonlinear controller based on the Lyapunov method, which is non-passive, and realizes precise position tracking of the UAV and suppression of the load swing, while maintaining the rope length within the desired range. Finally, the stability and convergence of the closed-loop system are proven through Lyapunov stability analysis and the LaSalle invariance principle. The simulation results show that the proposed method exhibits significant advantages in UAVs’ position, rope length tracking, and load swing suppression compared to the traditional lifting control strategy, and has strong robustness against uncertain parameters and external disturbances, verifying the effectiveness and practical value of the proposed method.